Financial Constraint Moderation : Tax Avoidance From The Perspective of Company And Executive Characteristics - Agung Wijaya; Tito Malindo (Journal of Economy, Accounting and Management Science (JEAMS), 2025)
This study ventures into uncharted waters by examining the Shaping force of executive temperament, capital intensity, and familial ownership on tax avoidance, with financial constraints as a moderating factor, a realm rarely explored within Indonesia's chemical sector. The aim is to dissect how managerial traits and ownership structures shape tax mitigation strategies, and to gauge the extent to which financial limitations amplify or temper these dynamics. Employing a quantitative approach, the study utilizes SEM, drawing on secondary data from chemical firms listed on the Indonesia Stock Exchange over a specified period. Revelations reveal that executive character and family ownership Considerablely bolster tax avoidance, whereas capital intensity exerts no notable effect. Financial constraints weaken the link between family ownership and tax avoidance but do not moderate other Interrelations. The study underscores the pivotal role of executive disposition and ownership concentration in crafting tax strategies, urging stricter oversight by tax authorities on firms with concentrated ownership. Its novelty lies in deploying financial constraints as a moderator within the unique asset and funding context of the chemical industry.